Experience with project-based learning in teaching spectroscopy with interdisciplinary groups - Gonzáles-Balladares, Julio David (2024)
The teaching of spectroscopy in university scientific initiation presents a challenge for science teachers, due to the need for specific analytical equipment. For this reason, this work proposes the design of three low-cost prototypes to be developed by interdisciplinary groups made up of fourth-cycle university students, applying project-based learning as an educational methodology to solve a problem of food adulteration. For this purpose, the students they must identify an extra virgin olive oil from a cheap vegetable oil using the principles of spectroscopy in their projects.